PENGARUH MUJA MATCAH BERBANTUAN METODE PROBLEM BASED LEARNING TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA : SEBUAH STUDI EKSPERIMENTAL - Siti Sholikah; Ida Putri Rarasati; Adin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problems raised are the lack of understanding and interest of students in fraction material and the limited use of technology-based learning media, which results in learning outcomes below the KKM. This study aims to explain the effect of Muja Matcah assisted by the problem-based learning method on interest and learning outcomes in mathematics partially and simultaneously. This study uses a quantitative approach with a quasi-experimental design in the form of a pretest-posttest non-equivalent control group. The subjects of the study involved 50 students, consisting of 25 students in class IV A and 25 students in class IV B at SD Negeri Kanigoro 03. Data analysis used the T test to see the effect partially and the MANOVA test to see the effect simultaneously. The results of the T test showed that Muja Matcah had a significant effect on learning interest  tcount  2.236> ttable 2.069, Sig. 0.035 < 0.05 and learning outcomes tcount  2.429 > ttable 2.069, Sig. 0.023 < 0.05. MANOVA test shows a significant effect on interest and learning outcomes, fcount interest 15.593 > ftable 4.26 and fcount results 53.721 > ftable 4.26. In conclusion, Muja Matcah assisted by problem based learning method has a significant effect on interest and mathematics learning outcomes of fourth grade students of SD Negeri Kanigoro 03, both partially and simultaneously.